2019
DOI: 10.3390/ijerph16162953
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Health Inequality in China and its Determinants: A Geographical Perspective

Abstract: Inter-regional health differences and apparent inequalities in China have recently received significant attention. By collecting health status data and individual socio-economic information from the 2015 fourth sampling survey of the elderly population in China (4th SSEP), this paper uses the geographical differentiation index to reveal the spatial differentiation of health inequality among Chinese provinces. We test the determinants of inequalities by multilevel regression models at the provincial and individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The medium and small cities were defined in accordance with the new standard for city-size classification in China (http://www.gov.cn/zhengce/content/2014-11/20/content_9225.htm). The urban population proportion, gross domestic product, income of residents, educational resources, sports resources, medical resources and air pollution in medium and small cities are less than those in large cities [2325]; all the data are illustrated in the Additional file 1: Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…The medium and small cities were defined in accordance with the new standard for city-size classification in China (http://www.gov.cn/zhengce/content/2014-11/20/content_9225.htm). The urban population proportion, gross domestic product, income of residents, educational resources, sports resources, medical resources and air pollution in medium and small cities are less than those in large cities [2325]; all the data are illustrated in the Additional file 1: Table S1.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies by Yan et al and Zhang et al analyzed the current situation of rural-urban disparities in healthcare resources in China (16,17). Fan et al reported that there were significant health differences in the elder population on an inter-provincial level, and nearly 2.4% of these health differences in the elder population were caused by inter-provincial inequalities (18). Zhu et al assessed the changes of regional disparities in traditional Chinese medical (TCM) healthcare resources before and after 2009 healthcare reforms, and reported that although TCM hospital number, scale, and doctors' workload increased in 2004-2016, the regional disparities in healthcare resources, especially between the eastern and western regions, were not significantly changed (19).…”
Section: Introductionmentioning
confidence: 99%
“…Other characteristics addressing SES include martial status and living arrangements. It has been demonstrated that being divorced or widowed is associated with poorer health because of marriage protection and selection effects [14]. As people grow older, they tend to benefit more from the impacts of marriage.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, unlike western countries, the Chinese household registration system is a dual system. Within this system, urban residents enjoy a range of social, economic, and cultural benefits, whereas rural residents do not receive the same benefits [14]. This system is closely associated with the social security system that excludes rural residents/migrant workers from the city-wide social security system [23].…”
Section: Introductionmentioning
confidence: 99%